ANALISIS STUDI KELAYAKAN PENGEMBANGAN USAHA JAMUR TIRAM PADA UD. KENANGA DI KELURAHAN AMPENAN SELATAN - IDA AYU KETUT MARINI; IDA BAGUS EKA ARTIKA (GANEC SWARA, 2023)
The purpose of this study is to determine whether or not the business development that will be carried out by UD. Memories in the South Ampenan Village of Mataram City when viewed from the investment criteria of Net Present Value (NPV), Pay Back Period (PP) and Profitability Index (IP). The data collection method used in this study is the case method or case study. In this case the case under study is the plan to add one unit of mushroom house (Kumbung) with a capacity of 500 baglogs. To find out the extent to which a business or business will be planned and can provide benefits or benefits, the analysis used is analysis of investment criteria. Based on the calculation of the Net Present Value, it shows that the total present value is Rp. 66,009,488.33, - which is greater than the initial investment of Rp. 12,630,000.00. So it shows a positive (+) net present value of IDR 53,379,488.33. The business development plan by adding one kumbung unit is feasible when viewed from the NPV investment criteria because the NPV results are positive (+). From the results of the payback period (PP) calculation above, it can be stated that cash inflow is needed in year 1 to cover the remaining the initial investment is Rp. 3,279,776.8 then the need for Rp. 3,279,776.8 only describes 38% of cash inflow in year 2 (3,279,776.8 : 8,598,866.0) X 1 year or in other words that cash inflow of IDR 3,279,776.8 in year 2 will be collected within 4 months 17 days. So the initial payback period from the investment plan is shorter than the economic life that has been set, which is 10 years, so that the plan to add 1 unit of kumbung is feasible. Based on the calculation of the profitability index above, it is obtained 5.2, this indicates that the plan to add 1 unit of kumbung is feasible because the PI value is > 1